Adaptive watermarking in spatial domain for still image - Kimpan, Somchok; Lasakul, Attasit; Kimpan, Chom (My University, 2004)
In this paper, watermarking for still image is proposed Image watermarking is performed in spatial domain that not only easy but also good result. A watermark image as binary image is embedded onto a original image by using method that gray levels of pixels in original image blocks is modified to appropriate an intensity of block. A variation of watermark image bits in order to embed the original image block selected affects to embedded block intensity and also it depends on original image block intensity. The block size is adapted as intensity of original image and capacity of watermark image in order to embed. As method of varying block size proposed, the effect of block size adaptation is good and also watermark image is robust to a number types of degradation. As the proposed method, qualify of the original image is at least affected.
Keywords: Spatial domain; Watermarking